(untitled) (Bangladesh Journal of Microbiology, 2016)
The essential oil of Pogostemon cablin (Blanco) Benth, also known as Patchouli oil was subjected for its antimicrobial investigation against a panel of ten human pathogenic bacteria and six human pathogenic fungi by Agar well diffusion method and Macrobroth dilution technique using Ampicillin (20ìg/well) and Nystatin (20ìg/well) as control. Antibacterial activity revealed that, the essential oil was more active against Gram positive bacteria than Gram negative bacteria. The largest zone of inhibition was 35 mm (against Bacillus cereus) with 20 ìl of oil. Ditermination of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) showed that, Bacillus cereus exhibited the lowest MIC (250 ìg/ml) and MBC (750 ìg/ml). The oil showed moderate antifungal activity against all tested organisms. Candida albicans showed greater zone of inhibition (16 mm) than Saccharomyces cerevisiae (14 mm) with 20 ìl and Candida albicans showed lowest MIC and MFC (both were 750 ìg/ml). The zone of inhibition was 25 mm for each filamentous fungal strain with 20 ìl, except for Rhizopus oligosporus (15 mm) and the lowest MIC (250 ìg/ml) and MFC (500 ìg/ml) were reported for Aspergillus fumigatus. Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 7-10